The Influence of Experience Quality, Attractiveness, and Accessibility on Revisit Intention Mediated by Electronic Word-of-Mouth (eWOM): A Survey of Tourists at Lembah Hijau - Algi Ahmad Kurniawan; Rahyono; Ayu Nursari (Yayasan Multidimensi Kreatif, 2026)
Nature-based tourism destinations face the challenge of maintaining stable revisit rates despite initial high visitor numbers . This study analyzes the influence of experience quality, attractiveness, and accessibility on revisit intention, with electronic word-of-mouth (eWOM) as a mediating variable. Focusing on the Lembah Hijau tourism area in Bandar Lampung , this research employed a quantitative approach with an exploratory survey design. The sample consisted of 396 tourists, selected using a non-probability sampling technique with the Slovin formula . Data were analyzed using multiple linear regression and the Sobel test via SPSS. The findings reveal that experience quality, attractiveness, and accessibility positively and significantly influence both eWOM and revisit intention. Mediation analysis indicates that eWOM significantly mediates the relationship between attractiveness and revisit intention, as well as accessibility and revisit intention. Interestingly, eWOM does not significantly mediate the effect of experience quality on revisit intention, suggesting that high-quality direct experiences drive loyalty independently of digital sharing . These results recommend that destination managers prioritize enhancing visual attractiveness and ease of access to stimulate positive eWOM, thereby strengthening long-term tourist loyalty.